Investigation of the Effects of a Self-Heated Vest on Vital Values of Individuals: A Case Study on Public Health - ÖZTEKİN, Erman Kadir; DEMİRCİ, Emre (International Journal of Computational and Experimental Science and Engineering, 2025)
With the adaptation of portable and harmless technological devices to clothing products, self-heating outdoor products are becoming more common in the market. These products can produce heat energy on their own, unlike standard thermally insulated products. In this way, it contributes to the thermal comfort of people in situations where the environment cannot be conditioned. In this study, the effects of these products, which are in close contact with the human body, on human health were measured through vital values. Measurements were collected from the same group of individuals at three different time intervals over 30 minutes. Significant differences between the obtained data were examined using the Friedman test and detailed using Wilcoxon Signed Rank test. While a significant difference was observed in systolic blood pressure, diastolic blood pressure and body temperature data, no significant difference was found in oxygen saturation and pulse data. As for the actual changes, no serious effects on human health were observed based on the vital values presented in the study.